2011
DOI: 10.11130/jei.2011.26.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Trade Flows in the Gulf Cooperation Council Countries : What happend to the Middle East Integration after 2003?

Abstract: It is well known that the GCC countries are heavily dependent on oil and hydrocarbon industries, but during the 2003-2008 period, economic diversification is proceeded; enhancing the role of the private sector, encouraging FDI, and laying the ground for competitive integration in the globalization process. The year 2003 is special for the economic integration within the GCC due to the introduction of the custom union and high growth. This paper analzes the trade flows of the GCC countries before and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Applying the gravity model in the Gulf Cooperation Council (GCC) countries, Boughanmi (2008) found that the GCC countries trade is twice more with each other than would be predicted by the basic gravity model. In another development, Insel and Tekce (2011) found that GCC countries trade are related to the wealth of the partner countries, but not their distance, mainly due to the nature of their exports and imports, the characteristics of the region and development in transport facilities. Similarly, in Asia, Kien (2009) Empirical studies on the Nigerian economy have been quite few.…”
Section: Literature Review and Theoretical Issuesmentioning
confidence: 99%
“…Applying the gravity model in the Gulf Cooperation Council (GCC) countries, Boughanmi (2008) found that the GCC countries trade is twice more with each other than would be predicted by the basic gravity model. In another development, Insel and Tekce (2011) found that GCC countries trade are related to the wealth of the partner countries, but not their distance, mainly due to the nature of their exports and imports, the characteristics of the region and development in transport facilities. Similarly, in Asia, Kien (2009) Empirical studies on the Nigerian economy have been quite few.…”
Section: Literature Review and Theoretical Issuesmentioning
confidence: 99%
“…Reference [11] investigated impact on bilateral trade flow of GCC countries before and after formation of custom union in 2003, using augmented gravity model. The panel least square and generalized method of movement (GMM) techniques are used to estimate the models.…”
Section: Review Of Literaturementioning
confidence: 99%